The effect of the type and composition of husk charcoal on the growth of shallots - Suriadi, Ahmad; Pranata, Rodi; Wahyuni, Ida (Jurnal Agrotek Ummat, 2024)
Shallots are a horticultural plant that is needed in large quantities as a vegetable, spice, and as an ingredient in traditional medicine. The high need and demand makes shallots economically valuable and efforts continue to be made to increase production output in the hope of being able to stabilize demand and affordable prices. This research aims to see the effect of the composition of adding husk charcoal on the growth of shallots. The method used in this research was an experimental method using a Completely Randomized Design (CRD) with direct experiments in a greenhouse. The composition of the husk charcoal used is reflected in the 4 treatments, namely T1 = 0% grilled husk charcoal biocompost + 100% soil (control), T2 = 25% grilled husk charcoal biocompost + 75% soil, T3 = 50% grilled husk charcoal biocompost + 50% soil, and T4 = 75% burnt husk charcoal biocompost + 25% soil. From these four treatments, growth was assessed, namely plant height, number of leaves, number of tillers, and plant weight (wet stem and dry stem). The research results were tested using mathematics using SPSS to see differences between treatments. The results of the research showed that the growth of shallots with the addition of different compositions achieved significant growth in the number of tillers and weight in wet and dry stems, while growth in height and number of leaves were not significantly different. So it can be concluded that with the composition of adding husk charcoal the highest number of tillers were in T3 and T4 while the highest weights were found in T1 and T2.